Development of the Revised Relational Maximization Scale and explorations of how relational maximization relates to personal and relational outcomes. (August 2020) - Mikkelson, Alan C.; Ray, Colter D.
Cheek and Schwartz argued for conceptualizing maximization as the goal of "choosing the best" coupled with the strategy of "alternative search." Using this conceptualization, we conducted five studies (Total N = 1, 617) to revise the Relational Maximization Scale. Two exploratory factor analyses (Exploratory Study and Study 1) confirmed that choosing the best and alternative search were empirically distinct. A confirmatory factor analysis (Study 2) demonstrated the strength of the factor structure for these two dimensions. Study 2 results also indicated that choosing the best correlated with rational and intuitive decision-making styles, whereas alternative search correlated with indecisive, avoidant, and intuitive decision-making styles. In Study 3, choosing the best was positively related to relational outcomes (e.g., satisfaction, commitment, and trust), whereas alternative search was negatively related to relational outcomes. Study 4 demonstrated that alternative search and the quality of alternatives were empirically distinct. Study 4 also showed that choosing the best was positively related to life satisfaction and optimism, whereas alternative search was positively related to regret and negatively related to optimism. Together, these studies validate the importance of examining domain-specific maximization in ongoing relationships and offer a new Revised Relational Maximization Scale. Specifically, we propose that the choosing the best subscale be used as a measure of the maximization goal and that the alternative search subscale be used as a measure of the maximization strategy.